IMPLEMENTASI BLENDED LEARNING UNTUK MENINGKATKAN KREATIVITAS DAN HASIL BELAJAR PADA MATA PELAJARAN EKONOMI PESERTA DIDIK KELAS XI IPS-2 SMAN 5 JEMBER SEMESTER GASAL TAHUN 2015/2016 - Sri Kantun; Raras Siswandini ASP (JURNAL PENDIDIKAN EKONOMI: Jurnal Ilmiah Ilmu Pendidikan, Ilmu Ekonomi dan Ilmu Sosial, 2015)
Blended learning is an evolving phenomenon that offers promise for addressing challenges such as students creativity, students learning outcomes and some aspects of academy. It has been is a teaching strategy that utilizes Internet technologies (E-Learning) combined with face-to-face in the classroom. These models have been applied in order to increase students’ creativity and learning achievement. This Class Action Research is in two cycles. It aims to improve student’s creativity and learning achievement in class XI IPS-2 SMA Negeri 5 Jember, school year of 2015/2016, on the subject of economics. This research refers to the Kemmis model that consists of four components: planning, implementation, observation, and reflection. The research was conducted in class XI IPS -2 SMA Negeri 5 Jember. The data was collected used observations, test, and interview. The data analysis used the quantitative descriptive analysis. The results show as follows: (1) Blended Learning can increase students' creativity. It can be seen from average scores on the observations, students' creativity increased from 47,5% (High) in first cycle, and 58,19% (Very High) in second-cycle. (2) Students learning outcomes after the implementation of Blended Learning has increased, the average percentage of scores is 68.73 on first-cycle and 75.04 on secondcycle.The percentage of mastery learning is 73%, on the first cycle, and 80% ont second cycle, (3). Students learning outcomes on affective score increase from 10,88 (on the level of High) on first cycle to 14,58 ( Very High) on second cycle.